Reconstruction of the Permian Period Climate - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2004)
Early Permian was the only geological period during which creatures with large spiny back-sails had evolved. These creatures included the reptiles Dimetrodon and Edaphosaurus as well as the amphibian Platyhystrix. An even earlier form of reptile, Ianthasaurus, existed which evolved a sail. This paper examines the body temperature variation of Dimetrodon during the different seasons of the year. The effect of the sail of Dimetrodon on its body temperature is also evaluated by means of a computer program written for this purpose and validated from experiments with a model animal. Many suggestions were proposed as to the function of the sail in a debate that lasted for a century. Among the first suggestions was the utilisation of the sail for camouflage, waiting for prey while among reeds, or for using the sail literally as a sail on a boat. Today the most widely accepted view is that the sail was used as a solar collector allowing Dimetrodon to absorb heat from the sun when it was cold in the morning. By warming up as fast as possible during the day, being a cold blooded animal Dimetrodon would have a distinct advantage over its prey and its rivals. The fact that at least two different types of spine bearing reptiles (Dimetrodon and Edaphosaurus) appeared and disappeared at approximately the same geological period suggested strongly that environmental factors may have given the spines significant survival value. In this study it is assumed that the sail was an important thermoregularity element of the animal. Therefore, instead of assuming weather conditions for the Permian period, those of Cyprus, which exhibit great diurnal and seasonal variations, are used in order to reconstruct the climate condition of the Permian period. It is shown that the sail of pelycosaurs provided an advantage to the reptile by warming it up quicker in the morning in cold environments. This would be a benefit, allowing Dimetrodon to prey on large reptiles, above 55 kg, in the early morning while they were sluggish. From the results presented a climate similar to that of March for Cyprus could be representative of that of the Permian period. When the climate became warmer the presence of the sail became unnecessary, increasing the body temperature above the lethal point. This may resulted in the extinction of these reptiles.
Keywords: Dimetrodon; Edaphosaurus